Ultrastructure of the Cell Wall of Erwinia amylovora - Huang, Pi-Yu (1971)
Thin sectioned cells of Erwinia amylovora revealed two electron-dense layers in their walls when fixed at 24 to 27 C and three when fixed at 4 C.